2022
DOI: 10.3390/medicina58070867
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Inflammatory Markers in Peri-Implantitis and Periodontitis Tissues: Digital vs. Manual Analysis—A Proof of Concept Study

Abstract: Background and Objectives: In dentistry, the assessment of the histomorphometric features of periodontal (PD) and peri-implant (PI) lesions is important to evaluate their underlying pathogenic mechanism. The present study aimed to compare manual and digital methods of analysis in the evaluation of the inflammatory biomarkers in PI and PD lesions. Materials and Methods: PD and PI inflamed soft tissues were excised and processed for histological and immunohistochemical analyses for CD3+, CD4+, CD8+, CD15+, CD20+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…PI and periodontitis (P) have many similarities in etiology, pathogenesis, diagnosis and treatment 6,7 . Thus, in the past, studies on the molecular mechanisms of peri‐implantitis and periodontitis had sought to reveal some important differences in histopathology and immunology 8,9 . Both diseases are opportunistic infections, but histopathology showed that PI has higher inflammatory regions 8,9 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PI and periodontitis (P) have many similarities in etiology, pathogenesis, diagnosis and treatment 6,7 . Thus, in the past, studies on the molecular mechanisms of peri‐implantitis and periodontitis had sought to reveal some important differences in histopathology and immunology 8,9 . Both diseases are opportunistic infections, but histopathology showed that PI has higher inflammatory regions 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Thus, in the past, studies on the molecular mechanisms of peri‐implantitis and periodontitis had sought to reveal some important differences in histopathology and immunology. 8 , 9 Both diseases are opportunistic infections, but histopathology showed that PI has higher inflammatory regions. 8 , 9 Even though the types of immune cells in both were similar, some studies had shown that the degree of immune infiltration was different, with PI having more plasma cells and lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation